Pengaruh Edukasi Melalui Aplikasi Tiktok Terhadap Pengetahuan Remaja Putri Kelas XI Tentang Pentingnya Konsumsi Tablet Tambah Darah Di MAN 2 Makassar - Diah Aulya, Hanifah; Andi Mansur Sulolipu; Fairus Prihatin Idris (Window of Public Health Journal, 2025)
Anemia is a micronutrient problem that occurs worldwide, especially in developing countries, with an estimated 30% of the world's population suffering from anemia. The prevalence of anemia in adolescents worldwide ranges from 40 to 88%. According to the World Health Organization (WHO), the incidence of anemia in adolescent girls in developing countries is around 53.7% of all adolescent girls. This study aimed to determine the effect of education through the TikTok application on the knowledge of eleventh-grade female adolescents about the importance of consuming iron tablets at MAN 2 Makassar in 2024. The method used is a quantitative method with a quasi-experimental approach. This study used non-parametric statistics, namely the Wilcoxon Signed Rank Test, to see the difference between knowledge before and after the intervention. Respondents were all eleventh-grade female students at MAN 2 Makassar. The population was 275 female students, with a sample size determined by the Slovin formula of 162 respondents. The sample was divided into two groups, where the experimental and control groups each consisted of 81 female students. The results of the study showed that the knowledge of female adolescents in grade XI obtained a p value = 0.000, which means p value <0.05. It can be concluded that education through the TikTok application has an influence on the knowledge of female adolescents in grade XI about the importance of consuming iron tablets at MAN 2 Makassar.